1992
DOI: 10.1182/blood.v79.8.2039.bloodjournal7982039
|View full text |Cite
|
Sign up to set email alerts
|

Factor IXa-factor VIIIa-cell surface complex does not contribute to the basal activation of the coagulation mechanism in vivo

Abstract: We have infused recombinant factor VIIa into patients with hereditary factor VII deficiency with marked reductions in plasma concentrations of factor IX activation peptide (FIXP), factor X activation peptide (FXP), and prothrombin activation fragment F1+2. These investigations show substantial elevations in these markers of coagulation activation and thereby demonstrate that the factor VII-tissue factor pathway is largely responsible for the activation of factor IX as well as factor X in the basal state (ie, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
24
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 0 publications
2
24
0
Order By: Relevance
“…34 The latter indicates the relative slow kinetics of factor VII activation, which consequently may result in protracted inhibition of TF by the zymogen. Some evidence for inhibition of thrombin generation in vivo by zymogen factor VII appeared from studies by Bauer et al 35 Infusion of a bolus of recombinant factor VIIa resulted in substantial fibrinopeptide A (FPA) generation in a completely factor VII-deficient patient, whereas no FPA generation was observed in a patient with a partial factor VII deficiency (16% antigen, 3% coagulant activity). Based on these results, Bauer et al hypothesized that the residual factor VII in the one patient inhibited the thrombin generation caused by factor VIIa in the completely factor VII-deficient patient; however, this hypothesis has not been substantiated so far.…”
Section: Discussionmentioning
confidence: 99%
“…34 The latter indicates the relative slow kinetics of factor VII activation, which consequently may result in protracted inhibition of TF by the zymogen. Some evidence for inhibition of thrombin generation in vivo by zymogen factor VII appeared from studies by Bauer et al 35 Infusion of a bolus of recombinant factor VIIa resulted in substantial fibrinopeptide A (FPA) generation in a completely factor VII-deficient patient, whereas no FPA generation was observed in a patient with a partial factor VII deficiency (16% antigen, 3% coagulant activity). Based on these results, Bauer et al hypothesized that the residual factor VII in the one patient inhibited the thrombin generation caused by factor VIIa in the completely factor VII-deficient patient; however, this hypothesis has not been substantiated so far.…”
Section: Discussionmentioning
confidence: 99%
“…17 Also, because plasma levels of FXP and prothrombin fragment F1.2 were normal in patients with severe hemophilia A or B, it could be concluded that FX and prothrombin activation were independent of the intrinsic FXase complex (i.e., FIXa and FVIIIa), at least under basal conditions. 18 More likely, the extrinsic Xase complex (i.e., TF-FVIIa) is responsible for this continuous low-level generation of FXa and thrombin, and the intrinsic Xase complex is recruited only after vascular injury. 18 This hypothesis was lent further support by experiments in normal chimpanzees in which infusion of a potent inhibitory monoclonal antibody to TF suppressed not only the basal level of activation of FIX and FX, but also the activation of FIX, FX, and prothrombin mediated by infusion of a high dose of recombinant FVIIa.…”
mentioning
confidence: 99%
“…The levels of factor VII/VIIa antigen and factor VII:C are shown in Table 1. Infusions of rFVIIa resulted in normalization of the levels of the activation peptides of factor IX, factor X, and prothrombin, 27 thereby corroborating the utility of such doses for patient treatment.…”
mentioning
confidence: 60%
“…In a research setting, we infused rFVIIa into two patients with congenital factor VII deficiency in order to investigate the pathways responsible for the activation of factor IX and factor X in vivo. 27 These patients had a bleeding diathesis but were asymptomatic and had not received factor VIIcontaining products for at least 5 days before investigation. Recombinant factor VIIa was administered to each patient at a dosage of 10 g/kg body weight followed several weeks later by a second infusion of rFVIIa at a dosage of 20 g/kg body weight.…”
mentioning
confidence: 99%